The Effect of Puzzle-playing on Fine Motor Development in Preschool Children - Ni Kadek Dian Arisanti; Anak Ayu Nyoman Trisna Narta Dewi; Agung Wiwiek Indrayani (Physical Therapy Journal of Indonesia, 2022)
Background: Development is developing human maturity and psychological processes that cannot be measured, such as increasing skills. The development speed in children is influenced by various factors such as the environment, health, nutrition, stimulation, and the role of parents. Fine motor development can be improved by applying the learning process and playing with interesting media, so children do not get bored easily. The media should be educative, like a puzzle game. Physiotherapy plays a role in preventing and reducing further complications that do not occur in children who experience fine motor delays. This research aims to determine the effect of giving puzzle games on fine motor development in preschool children. Methods: The method applied is a literature study by looking for theoretical references related to the research carried out. This literature review uses secondary data and information from journals collected from the Google Scholar, PubMed, and ScienceDirect databases over the last ten years as data sources. Results: Four studies discuss the impact of puzzle games on the fine motor development of preschool children. According to all journals, puzzle games impact the fine motor development of preschool-aged children. On average, about 25 children participate in each study. Conclusion: The findings obtained based on the literature that has been reviewed and the discussion state that giving puzzle games affects fine motor development in preschool children. The findings of this research can be used as a basis for puzzle therapy in children and are expected to be used to improve children's fine motor development through other games. There isn’t any clinical implication from this literature review.